Pengaruh Bi Rate, Inflasi, Fluktuatif Kurs Dan Volume Perdagangan Saham Terhadap Indeks Harga Saham Gabungan Periode 2009-2017 - Herlina dan Indra Widjaja (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The capital market is the liaison between investors and companies or within the government. Over the past few years, stock prices in Indonesian stocks have shown improved performance. JCI movement reflects the financial condition of business companies in Indonesia. Changing conditions can give positive or negative information on commercial transactions. Based on the results of the research, simultaneous macro variables are BI Rate, inflation, volume and trading volume that have a significant influence on JCI with sig value of 0.000 <0.01. While partially, BI rate and trading volume have a significant influence on JCI with BI sig rate of 0.000 <0,05 and trading volume sig 0.002 <0.01. The exchange rate and the exchange rate have no influence on the JCI with the sig value of inflation of 0.940> 0.05 and the fluctuating sig exchange rate of 0.584> 0.05.